Edukasi Pendidikan Agama Kristen Bagi Remaja di GKSI Sengkuang dalam Mengatasi Krisis Identitas - Lenvi Harefa; Novita Laia (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Teenagers at GKSI Sengkuang face similar struggles to teenagers in general. They are exposed to various influences that can weaken the foundations of their faith, such as unlimited access to social media, content that is not in line with Christian values, and relationships that are far from the principles of God's word. In situations like this, many teenagers experience confusion in determining who they are, what their purpose in life is, and how to live a life centered on Biblical values. Meanwhile, the research method uses qualitative by conducting direct observations, then the results of the observations will be processed into PKM articles, and supported by various literary sources such as journals, books, the Bible. The results of the research findings lie in the significant positive impact for GKSI Sengkuang youth. As well as, raising awareness of the dangers of identity crises, helping teenagers reflect on their self-worth in Christ, and growing their understanding of social pressures and the importance of church community.